Analysis Of Humidity, Temperature, Working Period, And Personal Protective Equipment In Home Industry At Gold Craftsmen - Nur Juliana; Anwar Mallongi; Wa Ode Megasari (Universitas Muhammadiyah Kalimantan Timur, 2021)
Home industries, especially at gold craftsmen in Malimongan Village, Makassar City, working indoors can experience pressure on hot and cold. In addition, the working period has been decades and used personal protective equipment are rarely used at gold craftsmen as protection from exposure of toxic in the work of environment. This study aims to analyze of humidity, temperature, working period, and used of personal protective equipment in home industry at gold craftsmen. This type of research is a descriptive survey. Direct collection was used a thermohygrometer, Samples of 30 houses, interviews through questionnaires at gold craftsmen amounted to 30 human sample were chosen using the simple random sampling. The analyzed using the frequency distribution of each variable. The results showed that the humidity in the room was mostly 66,7% not eligible requirements and 33,3% qualified requirements, an average of 62,90%. Most of the air temperature 86,7% not eligible requirements and 13,3% qualified requirements, an average of 32,430C. The working period at gold craftsmen >5 years is 96,7% and working <5 years is 3,3%, the working period between 3-32 years, an average of 15,57 years. Respondents never used of personal protective equipment such as face mask 93,3% and 6,7% sometimes used by towel for cover their nose. It is expected in home industry needs to increase ventilation in the workspace so that air of circulation can enter properly. In addition, at gold craftsmen need used of personal protective equipment while working.